The Ethical Commitment of Business Strategy: ESG-Related Factors as Drivers of the SDGs - López-Cabarcos, M. Ángeles (Journal of business ethics, 2025)
Companies play an important role in sustainable development. While many companies have incorporated ESG initiatives into their strategies, the specific impact of these efforts on the SDGs remains unclear, especially regarding how these initiatives are prioritized or aligned within corporate strategies. Despite the common relationship between ESG practices and sustainability, limited research has investigated how ESG strategies contribute to the SDGs. This paper aims to assess the ethical commitment of organizational practices, analysing how the combination of five ESG-related variables (ecological impacts, access and affordability, labour practices, product design and lifecycle management, and business ethics) leads to a positive contribution to the SDGs among 137 companies belonging to EUROSTOXX and S&P500 indexes. A fsQCA analysis has been conducted, distinguishing between ESG variables with internal, external, human and non-human connotations. The findings highlight that the combination of all these variables rather than isolated ESG practices is essential to achieve the SDGs. Although differences are shown between the companies belonging to the two indexes, ethical governance, environmental issues and labour practices have emerged as the most relevant ESG variables for achieving sustainable goals. This study provides a better understanding of what and how ESG initiatives can contribute to the SDGs, helping companies and policy makers identify the ethical approaches to consider when designing strategies to advance towards sustainable performance.